IMPROVING THROUGHPUT AND COMPLETION DATE ESTIMATION IN HIGH PRECISION COMPONENT MANUFACTURER USING SIMULATION APPROACH - S.Y., Gan; K.E., Chong, (Journal of Advanced Manufacturing Technology (JAMT), 2014)
Simulation has become an indispensable tool which enables engineers, designers, planner and managers, to study, analyze and evaluate complex situations that would not be otherwise possible. In this paper, a job shop simulation model with stochastic variables and constraints in a high precision component manufacturer is presented. Data was collected from the manufacturer of high-mix and low volume products, each product with different processing specifications. A discrete event simulation model was developed using the Witness Simulation software. The model is then verified and validated with the data from the company. Simulation experiments were conducted to identify bottlenecks in the manufacturing system and to test several scenarios of operators’ overtime. The experiments also have the ability to estimate the completion date for customer orders. Results show that simulation model gives better estimates of the completion dates of the customer orders compared to the production planner of the company.